(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Modification of plastic waste to be use as a replacement of coarse aggregate on the manufacturing of porous concrete block is presented in this paper. Different proportions of sand content were used with percentage of 1%, 5% and 10% by total weight of the sample to investigate its effects on the performance of porous concrete blocks based on some conducted tests i.e., compression and flexural load resistance, porosity, and infiltration rate tests. The results show that the porous concrete block with 5% of sand addition showed better strength properties compared to other mixtures. With 5% modified PET coarse aggregate, the compressive strength decreased for about 26%. Similar trends can be also observed when using PP and HDPE plastic aggregate. However, the inclusion of PET aggregate in porous concrete blocks with 5% of sand inclusion does not significantly show better strength indicating the weak bonding between plastic and cement mortar was performed in porous concrete block matrix as evident through the Scanning Electron Microscopy analysis. The formation of pores and higher permeability can be also expected after adding PET plastic waste as seen in porosity and infiltration rate results. Furthermore, the utilization of coarse aggregate made from plastic waste in porous concrete blocks containing fine aggregate is a potential solution on plastic waste management for permeable pavement including foot traffic and light load application.